An Analysis of Recount Text in English Textbooks Used by Tenth Grade Students - Sianipar, Riana br.; Sianturi, Dewi Sartika; Situmorang, Sintia Anastasia; Gulo, Perius; Saragih, Erikson (JOLLT Journal of Languages and Language Teaching, 2020)
This study was aimed at investigating the extent to which recount texts in two selected English textbooks meet the recount text criteria and to find out the similarities and differences of the recount texts between the two selected English textbooks. This study employed a descriptive qualitative method. The data in this study were four forms of recount texts taken from the two selected textbooks. Data analysis was done through analyzing, displaying, reducing, and drawing a conclusion. The data of this study include the generic structure, social objectives, and linguistic elements. The results of the analysis showed findings as follows: (1) four forms of the recount texts in the English textbooks have met the generic structure criteria, namely orientation, event, and reorientation; (2) one of the four recount texts fulfilled social goals; and (3) the four recount texts fulfilled the linguistic element. In short, the recount texts in English textbooks were similar to in terms of linguistic elements and type of process, while differences were found in terms of social goals and generic structure.